Hubungan antara Stres Akademik dan Adiksi Internet dengan Self-control sebagai Moderator - Siti Annisa Nugraheni; Siti Qodariah (Bandung Conference Series: Psychology Science, 2024)
Abstract. Studies that discuss the relationship between academic stress and internet addiction produce varying strengths of the relationship ranging from weak to strong. The study was conducted to see whether the role of self-control as a moderator variable can affect the relationship between academic stress and internet addiction. This study used a quantitative approach with 104 participants from Bandung City University students who also live in Bandung City, aged 18-25 years, experiencing academic stress, and internet addiction according to Young's (2011) criteria. Data were collected by independently filling out questionnaires by respondents to measure research variables, Student-life stress inventory (SLSI) to measure academic stress, Internet Addiction Test (IAT) to measure internet addiction, and Brief Self-control Scale (BSCS) to measure self-control. From the data analysis, several results were found. First, academic stress is positively correlated with internet addiction. Second, self-control negatively moderated the relationship between academic stress and internet addiction among university students in Bandung City. The findings emphasise the predictor role of stress on internet addiction and the role of self-control in the relationship between the two variables, and also provide insights into interventions in college students' excessive internet use behaviour for educators and practitioners, such as reducing academic stress levels and increasing self-control abilities. Abstrak. Penelitian-penelitian yang membahas hubungan antara stres akademik dan adiksi internet menghasilkan kekuatan hubungan yang bervariasi mulai dari lemah hingga kuat. Penelitian dilakukan untuk melihat apakah peran self-control sebagai variabel moderator dapat memengaruhi hubungan antara stres akademik dan adiksi intenet. Penelitian ini menggunakan pendekatan kuantitatif dengan partisipan berjumlah 104 mahasiswa Perguruan Tinggi Kota Bandung yang juga berdomisili di Kota Bandung, berusia 18–25 tahun, mengalami stres akademik, dan adiksi internet sesuai kriteria Young (2011). Data dikumpulkan dengan pengisian kuesioner secara mandiri oleh responden untuk mengukur variabel penelitian, Student-life stress inventory (SLSI) untuk mengukur stres akademik, Internet Addiction Test (IAT) untuk mengukur adiksi internet, dan Brief Self-control Scale (BSCS) untuk mengukur self-control. Dari hasil analisis data ditemukan beberapa hasil. Pertama, stres akademik berkorelasi positif dengan adiksi internet. Kedua, self-control memoderasi secara negatif hubungan antara stres akademik dan adiksi internet pada mahasiswa di Kota Bandung. Temuan ini menekankan peran prediktor stres terhadap adiksi internet dan peran self-control dalam hubungan kedua variabel tersebut, dan juga memberikan wawasan tentang intervensi dalam perilaku penggunaan internet yang berlebihan oleh mahasiswa bagi para pendidik maupun praktisi, seperti mengurangi tingkat stres akademik dan meningkatkan kemampuan self-control.